A Systematic Analysis of Islamic and Legal Perspectives on The Rights of Persons with Disabilities (PWDs) - Nurul Nadia Nozlan,; Azman Ab. Rahman; Hasnizam Hashim (USIM Press, 2024)
Journal of Quran Sunnah Education and Special Needs Volume 5 No.2 Page (60-70)